Peran Institusi dalam Teori Perdagangan Internasional dan Implikasinya untuk Pembangungan Ekonomi - Muhammad Fayyadh Akbar; Muhammad Zeki Abdillah; Muhammad Ali Syahbana; Aryadanu Dalimunthe (Jurnal Ekonomi dan Pembangunan Indonesia, 2025)
International trade plays a vital role in driving sustainable global economic growth. Institutions such as the WTO, IMF, and the World Bank contribute to regulating and facilitating fair and efficient global trade. This study examines the role of institutions in international trade and their impact on economic development. Using qualitative methods, the study shows that institutions help reduce trade barriers, enhance economic stability, and encourage sustainable innovation and investment. The results show that institutions play a key role in ensuring trade that contributes positively to global economic growth.